Old drug, new tricks: the utility of metformin in infection and vaccination responses to influenza and SARS-CoV-2 in older adults - Martin, Dominique E.; Cadar, Andreia N.; Bartley, Jenna M. (Frontiers in Aging, 2023)
In the face of global pathogens such as influenza (flu) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), strategies beyond standard vaccines and virus-specific treatments are critically needed for older populations who are more susceptible to severe disease and death from these infections due to age-related immune dysregulation. Thus, complimentary therapeutics are needed to address the increased risk of complications and death in older adults. Metformin, an FDA approved diabetes drug, is an attractive therapeutic candidate to improve immune defenses and resilience in older adults facing viral challenge. Metformin is already a candidate anti-aging drug, but its benefits have potential to span beyond this and improve specific immune responses. Metformin can target multiple aging hallmarks as well as directly impact innate and adaptive immune cell subsets. Both retrospective and prospective studies have demonstrated metformin’s efficacy in improving outcomes after SARS-CoV-2 or flu infections. Moreover, evidence from clinical trials has also suggested that metformin treatment can improve vaccination responses. In totality, these findings suggest that metformin can improve age-related declines in immunological resilience. Strategies to improve outcomes after infection or improve vaccine-induced protection are invaluable for older adults. Moreover, the ability to repurpose an already FDA approved drug has significant advantages in terms of necessary time and resources. Thus, metformin has great potential as a therapeutic to improve age-related immune dysregulation during flu and SARS-CoV-2 infections and should be further explored to confirm its ability to improve overall immunological resilience in older adults.